Constitutional fragments societal constitutionalism and globalization - Teubner, Gunther (Oxford : Oxford University Press, 2012)
The powerful private sectors of the world economy remain unconstrained by fundamental constitutional rules, leading to human rights abuses on a massive scale. This book examines how the values of constitutional governance can be applied to the private sphere in the modern world, through a network of constitutional fragments.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Keywords: Constitutional law; Administrative law; International business enterprises -- Law and legislation; Corporate governance; Law and globalization